Musikschaffen und Urheberrecht Schutzfähigkeit und Schutzbereich im Lichte vorbekannter Werke - Stumpf, Aaron Christopher (Abhandlungen zum Urheber- und Kommunikationsrecht, 2023)
To what extent may a piece of music be inspired by another without infringing copyrights? What is the role of originality and freedom of ideas in this context? When does such a piece maintain a sufficient distance to the protected work or fall under the exception for pastiches? The dissertation answers these questions with regard to the legal development in Germany and Europe. Copyright principles and doctrines are not only examined in their application to musical contexts, but are also fundamentally challenged on the basis of the findings. The dissertation thus offers a practice-oriented analysis of relevant criteria of music copyright law on the one hand, and questions the fundamentals of copyright law on the other.